Heat removal in axial flow high pressure gas turbine - Alhajeri, Hamad (Cranfield University, 2016)
The demand for high power in aircraft gas turbine engines as well as industrial gas turbine prime mover promotes increasing the turbine entry temperature, the mass flow rate and the overall pressure ratio. High turbine entry temperature is however the most convenient way to increase the thrust without requiring a large change in the engine size. This research is focused on improving the internal cooling of high pressure turbine blade by investigating a range of solutions that can contribute to the more effective removal of heat when compared with existing configuration. The role played by the shape of the internal blade passages is investigated with numerical methods. In addition, the application of mist air as a means of enhanced heat removal is studied. The research covers three main area of investigation. The first one is concerned with the supply of mist on to the coolant flow as a mean to enhancing heat transfer. The second area of investigation is the manipulation of the secondary flow through cross-section variation as a means to augment heat transfer. Lastly a combination of a number of geometrical features in the passage is investigated. A promising technique to significantly improve heat transfer is to inject liquid droplets into the coolant flow. The droplets which will evaporate after travelling a certain distance, act as a cooling sink which consequently promote added heat removal. Due to the promising results of mist cooling in the literature, this research investigated its effect on a roughened cooling passage with five levels of mist mass percentages. In order to validate the numerical model, two stages were carried out. First, one single-phase flow case was validated against experimental results available in the open literature. Analysing the effect of the rotational force, on both flow physics and heat transfer, on the ribbed channel was the main concern of this investigation. Furthermore, the computational results using mist injection were also validated against the experimental results available in the literature. Injection of mist in the coolant flow helped achieve up to a 300% increase in the average flow temperature of the stream, therefore in extracting significantly more heat from the wall. The Nusselt number increased by 97% for the rotating leading edge at 5% mist injection. In the case of air only, the heat transfers decrease in the second passage, while in the mist case, the heat transfer tends to increase in the second passage. Heat transfer increases quasi linearly with the increase of the mist percentage when there is no rotation. However, in the presence of rotation, the heat transfers increase with an increase in mist content up to 4%, thereafter the heat transfer whilst still rising does so more gradually. The second part of this research studies the effect of non-uniform cross- section on the secondary flow and heat transfer in order to identify a preferential design for the blade cooling internal passage. Four different cross-sections were investigated. All cases start with square cross-section which then change all the way until it reaches the 180 degree turn before it changes back to square cross-section at the outlet. All cases were simulated at four different speeds. At low speeds the rectangle and trapezoidal cross-section achieved high heat transfer. At high speed the pentagonal and rectangular cross-sections achieved high heat transfer. Pressure loss is accounted for while making use of the thermal performance factor parameter which accounts for both heat transfer and pressure loss. The pentagonal cross-section showed high potential in terms of the thermal performance factor with a value over 0.8 and higher by 33% when compared to the rectangular case. In the final section multiple enhancement techniques are combined in the sudden expansion case, such as, ribs, slots and ribbed slot. The maximum heat enhancement is achieved once all previous techniques are used together. Under these circumstances the Nusselt number increased by 60% in the proposed new design.